Analysis of failures in the launch of new products in the beverage industry in Peru from the stage-gate model - Alvarado Alarcón, Miluska (2018)
This article analyses the importance of properly structuring the process of the newproducts development (NPD). It identifies some failures in the NPD process in thePeruvian beverage industry based on an exploratory study of multiple cases of newproducts that failed to be launched on the market. A qualitative methodology was used to understand the NPD process, taking as a reference the stage-gate model since it’s one of the most sophisticated and disseminated innovation models in current practice. The study founded that the companies analysed made serious mistakes in their NPD processes, such as not listening to the consumer’s voice since the beginning of the process and not conducting pilot market tests, among others.